Enhanced Fatigue Strength of Commercially Pure Ti Processed by Rotary Swaging - Hasan ALkhazraji; Ehab El-Danaf; Manfred Wollmann; Lothar Wagner (Advances in Materials Science and Engineering)
Fully reversed bending fatigue tests were performed on polished hour-glass specimens of commercially pure titanium grade 1 with three different grain sizes, that were produced by severe plastic deformation (rotary swaging) and subheat treatments, in order to examine the effect of grain size on fatigue. An improvement in fatigue strength was observed, as the polycrystal grain size was refined. The endurance limit stress was shown to depend on the inverse square root of the grain size as described empirically by a type of Hall-Petch relation. The effect of refining grain size on fatigue crack growth is to increase the number of microstructural barriers to the advancing crack and to reduce the slip length ahead of the crack tip, and thereby lower the crack growth rate. It was found that postdeformation annealing above recrystallization temperature could additionally enhance the work-hardening capability and the ductility of the swaged material, which led to a marked reduction in the fatigue notch sensitivity. At the same time, this reduction was accompanied with a pronounced loss in strength. The high cycle fatigue performance was discussed in detail based on microstructure and mechanical properties.